Intervención urbana en el Malecón de la Ribera del Río de Oro en el Municipio de Girón, Santander - Villarreal Meza, Diana Carolina; Galvis Acevedo, Nancy Johana (Universidad Antonio Nariño, 2022)
The Urban Intervention on the Malecón de la Ribera del Río de Oro in Girón seeks to strengthen the municipality, which is part of the Metropolitan Area and is a National Monument of Colombia (Colombian Institute of Anthr opology and History, 2021). This has motivated great interest in the Girón tourist boardwalk, between Las Iguanas Park and the vehicular bridge of Carrera 25.